To find the corresponding point \( A' \) after dilation, we will use the center of dilation \( (h, k) = (-2, -1) \), the original point \( A(-3, 1) \), and the dilation factor \( m = 2 \).
The formula for the dilation of a point \( (x, y) \) about a point \( (h, k) \) is given by:
\[ (x', y') = (h + m(x - h), k + m(y - k)) \]
Plugging in the values:
- \( h = -2 \)
- \( k = -1 \)
- \( m = 2 \)
- \( A = (-3, 1) \)
We calculate:
-
Calculate \( x' \): \[ x' = -2 + 2(-3 - (-2)) = -2 + 2(-3 + 2) = -2 + 2(-1) = -2 - 2 = -4 \]
-
Calculate \( y' \): \[ y' = -1 + 2(1 - (-1)) = -1 + 2(1 + 1) = -1 + 2(2) = -1 + 4 = 3 \]
So the dilated point \( A' \) is
\[ A' = (-4, 3) \]
Thus, the corresponding ordered pair at point A after dilation is:
Response: (−4, 3)